Growth and reproductive characteristics in heifers fed endophyte-infected tall fescue and oxytetracycline - Peters, C.W.; Brazle, F.K.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Heifers developed on high-endophyte, tall fescue gained half as much weight (56 vs 117 lb; P<.01) and had a lower 35-day pregnancy rate (15 vs 58%; P<.01) compared to heifers fed low endophyte, tall fescue. Based on progesterone serum concentrations and visual determination of estrus, the proportion of heifers that had attained puberty by the start of the breeding season tended (P=.11) to be greater when fed oxytetracycline (55 vs 68%).
Keywords: Beef; Tall fescue; Reproduction; Puberty; Beef heifers; Oxytetracycline